2010
DOI: 10.1016/j.jfa.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

On the classical limit of Bohmian mechanics for Hagedorn wave packets

Abstract: We consider the classical limit of quantum mechanics in terms of Bohmian trajectories. For wave packets as defined by Hagedorn we show that the Bohmian trajectories converge to Newtonian trajectories in probability.Comment: some minor changes; published versio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Semiclassical wave packets. In [33] a result similar to Theorem 3.1 (ii) is proved, for the case of semiclassical wave-packets (see also [16] for a closely related study). The corresponding initial data are of the form (6.2) ψ ε 0 (x) = ε −d/4 a 0…”
Section: Numerical Simulation Of Bohmian Trajectoriesmentioning
confidence: 74%
“…Semiclassical wave packets. In [33] a result similar to Theorem 3.1 (ii) is proved, for the case of semiclassical wave-packets (see also [16] for a closely related study). The corresponding initial data are of the form (6.2) ψ ε 0 (x) = ε −d/4 a 0…”
Section: Numerical Simulation Of Bohmian Trajectoriesmentioning
confidence: 74%
“…One should note that the mathematical methods used in [9] are rather different from ours and that no convergence result for P ε (t) is given, except for p 0 = 0 (and, as a variant, for a class of time-averaged Bohmian momenta). In comparison to that, the use of β ε (t), together with classical Young measure theory, allows us to conclude the following result:…”
Section: Resultsmentioning
confidence: 91%
“…Finally, we shall consider the particular case where the initial data ψ ε 0 is a socalled semi-classical wave packet, see Theorem 2.3 below. The classical limit of Bohmian trajectories in this particular situation has been recently studied in [9]. There it has been shown that the Bohmian trajectories X ε (t, x) converge (in some suitable topology) to X(t), the classical particle trajectory induced by the Hamiltonian system…”
Section: Resultsmentioning
confidence: 99%
“…0 C . Indeed, it has been proved in [44] that for the case of semiclassical wave packets, convergence of the Bohmian flow to its corresponding classical counterpart holds in some appropriate topology (see also [21] for a closely The main differences between WKB states and semiclassical wave packets are that for the latter, the particle density concentrates in a point, i.e., " 0 .x/ "!0 C ! ı.x x 0 / in D 0 .R d /, and that the corresponding classical phase space flow does not exhibit caustics; cf.…”
Section: Semiclassical Wave Packetsmentioning
confidence: 99%